Structural Enhancement in Shallow Gas Cloud Region. (30th January 2015) - Latiff, A H Abdul; Ghosh, D P; Jamaludin, S N F
Abstract: This research will address the issue of poor structural interpretation below complex overburden and shallow anomaly that cause wave field distortion. The main objective of this research paper is to present the result of seismic interpretation over a seismic line extracted from a shallow gas filed located in Malay Basin. The readers will be briefly explained on the seismic data properties of shallow gas cloud, followed by methodology and techniques used in interpreting the data. Interpretation techniques used in this research work include the seismic data analysis based on the seismic attributes. The outcome from this work aims at recovering the hidden structure that cannot be seen in the data after processing and imaging sequences.